Characterization and rescue of telomeric abnormalities in ICF syndrome type I fibroblasts - Yehezkel, Shiran; Shaked, Rony; Sagie, Shira; Berkovitz, Ron; Shachar-Bener, Hofit; Segev, Yardena; Selig, Sara (Frontiers in Oncology, 2013)
Mutations in the human DNA methyltransferase 3B (DNMT3B) gene lead to ICF (immunodeficiency, centromeric region instability, facial anomalies) syndrome type I. We have previously described a telomere-related phenotype in cells from these patients, involving severe hypomethylation of subtelomeric regions, abnormally short telomeres and high levels of telomeric-repeat-containing RNA (TERRA). Here we demonstrate that ICF-patient fibroblasts carry abnormally short telomeres at a low population doubling and enter senescence prematurely. Accordingly, we attempted to rescue the senescence phenotype by ectopic expression of human telomerase, which led to elongated telomeres with hypomethylated subtelomeres. The senescence phenotype was overcome under these conditions, thus dissociating subtelomeric-DNA hypomethylation per se from the senescence phenotype. In addition, we examined whether the subtelomeric methylation could be restored by expression of a normal copy of full length DNMT3B1 in ICF fibroblasts. Ectopic expression of DNMT3B1 failed to rescue the abnormal hypomethylation at subtelomeres. However, partial rescue of subtelomeric-hypomethylation was achieved by co-expression of DNMT3B1 together with DNA methyltransferase 3-like (DNMT3L), encoding a protein that functions as a stimulator of DNMT3A and DNMT3B. DNMT3B1 and DNMT3L are predominantly expressed during early embryonic development, suggesting that de novo subtelomeric DNA methylation during crucial stages of human embryonic development may be necessary for setting and maintaining normal telomere length.